Sufism and Faith - Babojonovna, Abdullaeva Surayyo (Miasto Przyszłości, 2023)
In the following article, Sufism and faith, moral and spiritual situations after the spread of Islam and the death of Muhammad have been studied. More comments that are extensive were made about Sufis, possessors of high spirituality. The religious views of the 11th-12th centuries and their correlation with the word and hadith were studied.